INTRIGUING VASCULAR ENCOUNTER: ANEURYSM ALONG AN ABERRANT SYSTEMIC ARTERY TO THE LUNG- RADIOLOGY CASE STUDY - Nikolova, Sonja; Dokoska, Marija; Dimitrijevikj, Kristina; Jakimovska Dimitrovska, Maja; Stojovska Jovanovska, Elizabeta (Journal of Morphological Sciences, 2024)
Systemic arterial supply to the lungs from an aberrant artery is a rare congenital anomaly, and the occurrence of an aneurysm along this aberrant vessel is an even rarer phenomenon. We present a detailed case study of a 69-year-old male diagnosed with a fusiform aneurysm of an aberrant systemic artery supplying the right lower lobe. Accurate diagnosis was achieved through CT angiography, enabling precise visualization of the anomalous artery and the aneurysmatic dilatation. In this unique case, a 69-year-old male presented with persistent cough, chest/back pain, dyspnea, prompting medical attention. Ultrasonography revealed an atypical dilation of the inferior vena cava (IVC), measuring up to 3.5 cm, alongside a distinct sub-hepatic vascular structure. Doppler imaging indicated a discernible signal, prompting further investigation through CT angiography. Notably, during imaging, features suggestive of intra-lobar sequestration were observed, indicating a potential connection between the vascular anomalies and eventual respiratory symptoms. Keywords: intra- lobar sequestration, aberrant systemic artery, aneurysm, CT angiography.